Compartmentalization Device of Microenvironment for Analyzing iPSCs Differentiation - Fukai, Daiki; Toyoda, Taro; Takao, Hidekuni; Shimokawa, Fusao; Terao, Kyohei (Electrical engineering in Japan, 2025)
ABSTRACT This paper reports on a microdevice for compartmentalizing the solution microenvironment that can fractionate the space surrounding spheroids during the culture and differentiation processes, with the aim of verifying the effects of cell–cell interactions in the solution microenvironment on iPS cell differentiation. In this paper, we demonstrated that spheroids of iPS cells were successfully formed on the device and fractionated their microenvironment by a detachable compartmentalization frame (DCF) formed by 3D printing technology.